Globalne dobra publiczne - Brol, Marcin (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The aim of this paper is to put the information about the global public goods in order. The old theory of public goods has been criticized by many authors. In the global economy some institutions cannot effectively distribute those goods. There is a need to rethink the concept of the public goods and to implement changes in the future. In this paper the author presents some new theoretical concepts originally presented by Inge Kaul. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 33-40